p518, a small floR plasmid from a South American isolate of Actinobacillus pleuropneumoniae - Cunha,da silva G; Rossi,CC; Santana,MF; Langford,PR; Bosse,JT; Bazzolli,DM (Veterinary Microbiology, 2017)
A small (3.9 kb) plasmid (p518), conferring resistance to florfenicol (MIC >8 μg/mL) and chloramphenicol (MIC >8 μg/mL) was isolated from an Actinobacillus pleuropneumoniae clinical isolate from Southeastern Brazil. To date, this is the smallest florfenicol resistance plasmid isolated from a member of the Pasteurellaceae. The complete nucleotide of this plasmid revealed a unique gene arrangement compared to previously reported florfenicol resistance plasmids found in other members of the Pasteurellaceae. In addition to the floR gene and a lysR gene, common to various florfenicol resistance plasmids, p518 also encodes strA and a partial strB sequence. An origin of replication (oriV) similar to that in the broad host range plasmid, pLS88, was identified in p518, and transformation into Escherichia coli MFDpir confirmed the ability to replicate in other species. Mobilisation genes appear to have been lost, with only a partial mobC sequence remaining, and attempts to transfer p518 from a conjugal donor strain (E. coli MFDpir) were not successful, suggesting this plasmid is not mobilisable. Similarly, attempts to transfer p518 into a competent A. pleuropneumoniae strain, MIDG2331, by natural transformation were also not successful. These results suggest that p518 may be only transferred by vertical descent.